CHALLENGING JOB DEMANDS AS A PREDICTOR OF WORK ENGAGEMENT AMONG TEACHERS: ROLE OF JOB BURNOUT - Ambar; Najma (The journal of contemporary issues in business and government, 2021)
Teaching as a profession has been considered to involve a wide range of job-related demands which required high flexibility and multidimensional skills. Though the teacher’s core business is to enhance the achievements and learning of students yet many other underrated tasks such as university administration and development, cooperation outside and within and the university are required from the teacher, which become potential stressors and consequently acknowledged as a crucial feature for their burnout and turnover.The current research aimed to investigate challenging job demands, work engagement and job burnout among purposively selected universityteachers from Punjab Province, Pakistan. Challenging Job Demands (Makhdoom, 2017), Ultra-Short Measure for Work Engagement (Schaufeli et al., 2017) and Oldenburg Burnout Inventory (Demerouti et al., 2010) questionnaires were used to measure the variables of the present research. Results showed that challenging job demandshad a positive predictive relationship with work engagement, which meansthat those teachers who perceive their job as challenging were more engaged in work. Mediation analysis through Process Macron(version 3.5) revealed job burnout significantly and partially mediated between challenging job demands and work engagement. The current study concluded that challenging job demands were a strong and positive predictor of work engagement among teachers. However, the present study also concluded a significant and partial mediating role of job burnout in the relationship of challenging job demands and work engagement of teachers. The present study has some recommendations for future researchers.